2019
DOI: 10.1038/s41398-019-0654-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabidivarin (CBDV) on brain excitation and inhibition systems in adults with and without Autism Spectrum Disorder (ASD): a single dose trial during magnetic resonance spectroscopy

Abstract: Autism spectrum disorder (ASD) is a high cost neurodevelopmental condition; and there are currently no effective pharmacological treatments for its core symptoms. This has led some families and researchers to trial alternative remedies – including the non-intoxicating Cannabis sativa-derived compound cannabidivarin (CBDV). However, how CBDV affects the human brain is unknown. Previous (pre)clinical evidence suggests that CBDV may modulate brain excitatory-inhibitory systems, which are implicated in ASD. Hence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 51 publications
3
64
0
1
Order By: Relevance
“…[80][81][82] Interestingly, in both the valproate model and Mecp2 mutant mice, CBDV reversed the alterations of eCBS proteins observed in the brain (such as the increased levels of CB 1 receptors). 80,82 In adults with ASD submitted to an MRS study, 83 CBDV (600 mg, single oral dose) produced, in the left basal ganglia, effects on glutamate-GABA signaling similar to those exerted by the same dose of CBD in the prefrontal cortex. 78…”
Section: Cbdvmentioning
confidence: 96%
“…[80][81][82] Interestingly, in both the valproate model and Mecp2 mutant mice, CBDV reversed the alterations of eCBS proteins observed in the brain (such as the increased levels of CB 1 receptors). 80,82 In adults with ASD submitted to an MRS study, 83 CBDV (600 mg, single oral dose) produced, in the left basal ganglia, effects on glutamate-GABA signaling similar to those exerted by the same dose of CBD in the prefrontal cortex. 78…”
Section: Cbdvmentioning
confidence: 96%
“…Participants were mainly children, even if in two studies there were mixed samples [53,54]. The three studies conducted by Pretzsch and colleagues [55][56][57] included only adults with normal cognitive abilities (IQ>70). Interestingly, only another study [58] has specified the level of functioning, which was not reported in the remaining papers.…”
Section: Characteristics Of Studies and Participantsmentioning
confidence: 99%
“…McVige et al [60] documented the use of medical cannabis with unspecified composition. Finally, Pretzsch and colleagues administered single doses of 600 mg of CBD or CBDV [55][56][57]. Only the studies by Pretzsch et al used a control treatment (placebo).…”
Section: Characteristics Of Treatmentmentioning
confidence: 99%
See 2 more Smart Citations